A Piece of Education on Comparative Performance Study of Islamic Banking system and Commercial Banking system in Pakistan - et. al., Dr. Khurram Sultan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose of the study: Islamic banking has been explained in numeral ways. This study is shown to find out the difference among the two parts of banking, the first one is Islamic banking and the second one is conventional banking system of Pakistan with respect to liquidity, efficiency, and profitability. The secondary data from banks of each banking subdivision is taken for valuation. Proportion analysis is used to define the characteristics of study respondents and regression analysis is used to study the difference in term of significant factors that affect client trust of Islamic banks and commercial banks. Methodology: The secondary data from banks of each banking area is taken for calculation. Ratio analysis is used to conclude the characteristics of study respondents and regression analysis is applied to examine the difference in term of significant factors that influence customer trust of Islamic banks and commercial banks. Five Islamic banks and five commercial banks has been taken as sample under population of all the banks Main Findings: The results of the study show that there is important difference among the both kinds of banking for the variables under study. Furthermore, influence of return on asset is more on client trust for the study period (2015– 2019) for the Islamic bank as compared to the conventional banking. The study also inspects the important factors that are significant for development of Islamic banking. Application of this study: This study contributes toward the financial area for policymakers in order to build the best policies of the banking system. New banks can get advantage form this study in order to achieve their goals this thing will ultimately lead toward the success.